2016
DOI: 10.1166/jnn.2016.12349
|View full text |Cite
|
Sign up to set email alerts
|

Using Gold Nanoparticles as Delivery Vehicles for Targeted Delivery of Chemotherapy Drug Fludarabine Phosphate to Treat Hematological Cancers

Abstract: Nanotechnology is an emerging paradigm for creating functional nanoscale materials for various biomedical applications. In this study, a new nanotechnology-based drug delivery method was developed using gold nanoparticles (GNPs) as a delivery vehicle to reduce adverse drug side effects. Fludarabine Phosphate is a commercial chemotherapy drug used in cancer treatment, and has ability to kill various cancer cells. KG-1 cell, a type of acute cancer leukemia cell, was selected as a proof-of-concept target in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Despite the high anti‐proliferative effect of free TS262 and TS265 in FR37‐CMT cells, it has been demonstrated that AuNPs are excellent carriers for drug delivery . To allow the direct comparison between free and nanoconjugated compounds, the effect of the NanoTS262 and NanoTS265 on FR37‐CMT cells viability was performed at IC 50 concentrations, both for the free compounds and the nanovectorized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high anti‐proliferative effect of free TS262 and TS265 in FR37‐CMT cells, it has been demonstrated that AuNPs are excellent carriers for drug delivery . To allow the direct comparison between free and nanoconjugated compounds, the effect of the NanoTS262 and NanoTS265 on FR37‐CMT cells viability was performed at IC 50 concentrations, both for the free compounds and the nanovectorized.…”
Section: Resultsmentioning
confidence: 99%
“…The high cytotoxic effect here demonstrated for the free TS262 and TS265 in the FR37‐CMT cell line, highlights their further application using novel nanodelivery systems. Owing to their size and ease of functionalization with different moieties (eg PEG for biocompatibility; BSA allowing the loading with the desired chemotherapeutics—here TS262 or TS265 as models) it has been demonstrated that AuNPs can act as promising carriers for drug delivery further increasing the therapeutic index . Despite the high number of applications of AuNPs as drug delivery agents in human cancer, as far as we are aware there is no description of their application in CMT.…”
Section: Discussionmentioning
confidence: 99%
“…However, biological delivery methods are highly cargo and host-specific (6) whereas particle bombardment can result in tissue damage (7). Nanomaterial-mediated biomolecule delivery has facilitated genetic engineering and biosynthetic pathway mapping in animal systems (8)(9)(10)(11)(12), but has only recently been explored for plants. Specifically, two recent studies have shown that carbon nanotubes (13) and clay nanosheets (14) enable passive intracellular delivery of DNA and RNA through surface-grafting or encapsulation strategies, circumventing the use of biolistics (external force).…”
Section: Introductionmentioning
confidence: 99%
“…While nanoparticle-mediated delivery of genes, RNAs, and therapeutics has been extensively explored in animals 15,16 , their potential for plant systems remains understudied 17 . Several prior studies take advantage of nanomaterials to deliver plasmid DNA [18][19][20][21] or proteins 22 to intact plant cells.…”
Section: Introductionmentioning
confidence: 99%